A Review of the Factors Associated With the Timely Initiation of Breastfeeding and Exclusive Breastfeeding in the Middle East. (15th December 2017) - Alzaheb, Riyadh A
Background: Breastfeeding supplies all the nutrients that infants need for their healthy development. Breastfeeding practice is multifactorial, and numerous variables influence mothers' decisions and ability to breastfeed. This review identifies the factors potentially affecting the timely initiation of breastfeeding within an hour after birth and exclusive breastfeeding in the first 6 months in Middle Eastern countries. Methods: The Medline, ScienceDirect, and Web of Science databases were keyword-searched for primary studies meeting the following inclusion criteria: (1) publication in the English language between January 2001 and May 2017, (2) original research articles reporting primary data on the factors influencing the timely initiation of breastfeeding and/or exclusive breastfeeding, (3) the use of World Health Organization definitions, and (4) Middle Eastern research contexts. A random effect model was used to establish the average prevalence of the timely initiation of breastfeeding and exclusive breastfeeding in the Middle East. Results: The review identified 19 studies conducted in Saudi Arabia (7), Iran (3), Egypt (2), Turkey (2), Kuwait (1), the United Arab Emirates (1), Qatar (1), Lebanon (1), and Syria (1). The meta-analysis established that 34.3% (confidence interval [CI]: 20.2%-51.9%) of Middle Eastern newborns received breastfeeding initiated within an hour of birth, and only 20.5% (CI: 14.5%-28.2%) were fed only breast milk for the first 6 months. The 8 studies exploring breastfeeding initiation most commonly associated it with the following: delivery mode, maternal employment, rooming-in, and prelacteal feeding. The 17 studies investigating exclusive breastfeeding most frequently linked it to the following: maternal age, maternal education, maternal employment, and delivery mode. Conclusions: Middle Eastern health care organizations should fully understand all the determinants of breastfeeding identified by this review to provide suitable practical guidance and advice to help new mothers to overcome barriers where possible and to contribute to improving infant and maternal health in the region.